Species Diversity of Laelapid Soil Mites (Acari: Laelapidae) Under Different Land Use Types in Saman and Shahrekord - M. Amani; J. Khajehali; F. Noorbakhsh; O. Joharch; M. R. Sabzalian (Iranian Journal of Applied Ecology, 2015)
Mites are the best representative of soil arthropods because they are the most diverse in terms of ecological niche and behavior. In this study, abundance and biodiversity of laelapid soil mites were evaluated in eight sites in Saman and Shahrekord, with each site including an orchard and a farmland. There was a significant difference in the Shannon-Wiener diversity index of laelapid mites among different land uses. The maximum value of this index was (0.44) in soil of elm trees in Shahrekord. The Margalef species richness index was highest (0.64) in an almond orchard in Saman. The maximum amount of the Simpson index was (0.39) in the almond orchard of Saman. The regression line equations and coefficient of determination between the soil organic matter and biodiversity indices were calculated. The results showed that the coefficient of determination (r2= 0.73) for soil organic matter and the Simpson index was higher than that of other indices. Therefore, it could be concluded that the response of laelapid soil mites conforms to the management practices of farmlands, changes in abundance of species, and biodiversity indices.